Selected Problems of Assessment in Teaching Philosophy - Ambrozy, Marián (Ruch Filozoficzny, 2023)
The present paper discusses selected issues of evaluation in the teaching of philosophy. It deals with the issue under consideration on a general level since we do not differentiate between high school and college study performance assessment. Critical reflection focuses on the proper mode of evaluation in teaching the history of philosophy as and in the disciplines of systematic philosophy. In doing so, the close interrelation between the history of philosophy and its disciplines is considered. Three basic evaluative approaches are distinguished. These vary depending on whether the assessment is of the history of philosophy, logic, or other philosophical disciplines. The question of whether a philosopher or a philosophy teacher not directly involved in discussing philosophical issues is better as an evaluator is also investigated. Furthermore, the paper also articulates the reasons for preferring the first option.